A historical analysis of the US stock price index using empirical mode decomposition over 1791-2015 - Aviral K. Tiwari; Arif B. Dar; Niyati Bhanja; Rangan Gupta (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
In this paper, the dynamics of Standard and Poor's 500 (S&P 500) stock price index is analysed within a time-frequency framework over a monthly period 1791:08-2015:05. Using the Empirical Mode Decomposition technique, the S&P 500 stock price index is divided into different frequencies known as intrinsic mode functions (IMFs) and one residual. The IMFs and the residual are then reconstructed into high frequency, low frequency and trend components using the hierarchical clustering method. Using different measures, it is shown that the low frequency and trend components of stock prices are relatively important drivers of the S&P 500 index. These results are also robust across various subsamples identified based on structural break tests. Therefore, US stock prices have been driven mostly by fundamental laws rooted in economic growth and long-term returns on investment.
Keywords: C22; G10; 330; Empirical Mode Decomposition; stock prices; S&P 500 Index; United States